Toxicidade aguda de clomazona, sulfentrazona, indaziflam e tebutiuron em macrófitas - Siqueira, Bruno Barbugian Ramalho (Universidade Federal de São Carlos, 2024)
The use of herbicides with a long residual can have an impact on the productivity of agricultural crops and cause negative effects on terrestrial and aquatic ecosystems due to surface run-off or leaching. In this context, the aim of this study was to evaluate the residual effect of the herbicides clomazone, sulfentrazone, indaziflam and tebutiuron and their acute effects (CE50; CENO and CEO) on different species of macrophytes: Lemna minor and Azolla caroliniana. The experiment was conducted in the laboratory according to OECD (2002) toxicity standards (CE50;7d; CENO and CEO) to analyze the effect of the herbicides at different concentrations, according to the ecotoxicological table, on the cultivation of L. minor and A. caroliniana, and thus evaluate mortality and fresh mass (g) over a period of 7 days. At the end of the work carried out in the laboratory, the data obtained from the acute tests was evaluated for the concentration that caused an acute effect on 50% of the organisms, which corresponds to the average effective concentration (EC50), and then calculated and compared with the average value shown on the laboratory control chart. The EC50 was calculated using the Trimmed Spearman-Karber statistical method (p < 0.05). To determine CENO and CEO, the data was analyzed for normality (Chi-Square test) and homogeneity of variances (Bartlett's test), and then for the difference between the two. Bartlett's test), followed by analysis of variance, using Dunnett's test to check for significant differences between the treatments and the control. The CE50 of the herbicides clomazone, sulfentrazone, indaziflam and tebutiuron were 0.41, 0.73, 0.12 and 0.21 mg.L -1, respectively, for the Lemna minor species. For the macrophyte Azolla caroliniana, the EC50 determined were 3.26 mg.L-1 for clomazone, 0.51 mg.L-1 for sulfentrazone, 0.11 mg.L-1 for indaziflam and 0.71 mg.L-1 for tebutiuron. All the herbicides showed moderate toxicity to both species species tested, causing significant reductions in fresh mass, even at lower concentrations.
Acute toxicity of clomazone, sulfentrazone, indaziflam and tebutiuron on macrophytes
Keywords: Herbicidas; Lemna minor; Ecotoxicologia; Fitotoxicidade; Azolla caroliniana; Herbicides; Ecotoxicology; Phytotoxicity; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA